Hubungan antara perubahan iklim dengan jumlah kasus demam dengue (DD) di Denpasar, Bali tahun 2010-2015 - I Gusti Agung Bagus Arya Wiradarma; I Ketut Agus Somia (DiscoverSys Inc., 2019)
Background: Dengue is one of tropical infectious disease that can give a serious public health problem in Denpasar. Several factors have been associated with the high prevalence of dengue fever; one of them is climate changes. This study aims to determine the relations between climate change and a number of dengue cases in Denpasar.Methods: The climate change and a number of dengue cases data take place in Denpasar from the year 2010-2015 using observational study. The Spearman correlation test was used to know the relation between climate change ( maximum and minimum temperature, rainfall, humidity, light duration, and wind velocity ) and a number of dengue cases. Data were analyzed using SPSS version 20 software for windows.Results: The highest prevalence of Dengue Fever infection was in 4,431 (38.16%) cases in 2010, followed by 1,837 (15,82%) cases in 2014, 1,766 (15.22%) cases in 2013, 1,576 (13.57%) cases in 2015, 1,009 (8.69%) cases in 2012, and 992 (8.54%) cases in 2011. Based on climate variables, rainfall has a weak significant relation affecting the number of dengue cases compared with others (r=0.247; p=0.036).Conclusion: Rainfall was the only climates variables significantly related to the high prevalence of dengue fever in Denpasar, Bali since 2010-2015. So, further efforts need to be done to prevent dengue cases on rainy season.